Profile of an occupation – specialist in market and social research - Schambeck, Arne [Verfasser] (My University, 2021)
"For many years, young people wishing to pursue a career in market and social research were forced to attend university first. Since the introduction of the training occupation of “specialist in market and social research” in 2006, however, they have been able to enter the sector directly. The three-year training programme imparts the knowledge required to deal with highly varying issues of societal and economic relevance in a versatile and differentiated way." (Author's abstract, BIBB-Doku)
Keywords: S 6.4 Dienstleistungsberufe; 370; Fachangestellter für Markt- und Sozialforschung; Berufsprofil